A Biologist's View of Individual Cultural Identity for the Study of Cities - Richard Pearce (Fondazione Eni Enrico Mattei (FEEM), 2003)
The behaviour of urban populations is compared with the systems directing behaviour in individuals. This is both a metaphor and a mechanistic parallel. The biological model draws upon recent developments in brain research and psychological and cultural anthropology. The development and operation of the personal value-system are seen as constituting Identity in an individual, and Culture in a community. A mechanism is proposed by which social attachments between individuals lead to the adoption of new values into the system. The ability to differentiate own group from other is seen as intrinsic and socially necessary, made peaceful by specific values and adversarial by others. Identity development is such a complex process that it cannot be predicted in detail, but explicated in retrospect. A model may be useful in understanding conflicts of values, and how some are modifiable and others not.
Keywords: Z10; 330; Identity; Cultural meaning system; Values; Attachment; Social identity theory